A sociological theory of privacy as a communicative right - Mark Hanna (Revista Direito Mackenzie)
This paper redefines informational privacy through the lens of Niklas Luhmann’s communication theory, shifting the focus from individual actions to a broader understanding of informational privacy within the theoretical framework of this thinker. While privacy studies have traditionally been influenced by action theory, this paper examines how societal expectations of informational privacy emerge and operate within communicative processes. Although Luhmann did not explicitly address privacy, his theory has been applied to this topic in a limited manner. Building on these applications, this paper provides a deeper perspective on informational privacy, framing it within Luhmann’s theory and analysing its role in the formation of legal and social norms.